A new TB vaccine, MVA85A, induces durable antigen-specific responses 14 months after vaccination in African infants - Odutola, A; Owolabi, O; Owiafe, P; Mcshane, H; Ota, M (2012)
This study aimed to evaluate the durability of the immunogenicity of MVA85A beyond infancy. Participants in an immunogenicity study of MVA85A administered at age of 4 months had additional evaluation 14 months after initial vaccination for IFN-γ ELISPOT responses to Ag85A peptide and ESAT6/CFP-10 and tuberculin skin test (TST).112 children participated in this study. The anthropometry, biochemical and haematological safety profile were similar between the MVA85A recipients and controls. MVA85A recipients still had significantly higher immune responses to Ag85A compared to the controls. The majority of these children had negative responses to the TST as well as the ESAT6/CFP-10 antigens. In summary, MVA85A-vaccinated children had a persistently higher Ag85A immune response 14 months following vaccination than controls. All the children had negligible evidence of latent infection with M. tuberculosis (Mtb), suggesting that deploying a prophylactic vaccine against Mtb infection at this age could still be effective in this setting. © 2012 Elsevier Ltd.